Plasma Extracellular Vesicles Enhance HIV-1 Infection of Activated CD4+ T Cells and Promote the Activation of Latently Infected J-Lat10.6 Cells via miR-139-5p Transfer - Okoye, Isobel; Xu, Lai; Oyegbami, Olaide; Shahbaz, Shima; Pink, Desmond; Gao, Priscilla; Sun, Xuejun; Elahi, Shokrollah (Frontiers in Immunology, 2021)
HIV latency is a challenge to the success of antiretroviral therapy (ART). Hence patients may benefit from interventions that efficiently reactivate the latent virus to be eliminated by ARTs. Here we show that plasma extracellular vesicles (pEVs) can enhance HIV infection of activated CD4+ T cells and reactivate the virus in latently infected J-Lat 10.6 cells. Evaluation of the extravesicular miRNA cargo by a PCR array revealed that pEVs from HIV patients express miR-139-5p. Furthermore, we found that increased levels of miR-139-5p in J-Lat 10.6 cells incubated with pEVs corresponded with reduced expression of the transcription factor, FOXO1. pEV treatment also corresponded with increased miR-139-5p expression in stimulated PD1+ Jurkat cells, but with concomitant upregulation of FOXO1, Fos, Jun, PD-1 and PD-L1. However, J-Lat 10.6 cells incubated with miR-139-5p inhibitor-transfected pEVs from HIV ART-naïve and on-ART patients expressed reduced levels of miR-139-5p than cells treated with pEVs from healthy controls (HC). Collectively, our results indicate that pEV miR-139-5p belongs to a network of miRNAs that can promote cell activation, including latent HIV-infected cells by regulating the expression of FOXO1 and the PD1/PD-L1 promoters, Fos and Jun.